Design and Development of Energy Efficient Lighting Controller - Saha, Amrita; Paul, Debabrata; Jana, Roni; Datta, Soham; Roy, Amartya (International Journal of Computer Sciences and Engineering, 2025)
In the paper we have developed a model classroom to use artificial light with respect to the incoming daylight with a purpose to save energy. The classroom is assumed to be divided into two parts according to the no. of occupant present and the region of operation will vary according to the presence of occupant in the working plane. Different sensors are used to obtain several data like Infrared sensor, Light sensor, occupancy sensor to obtain no. of occupant, daylight and region of presence of occupant. A microcontroller is used to which is connected with the sensors to obtain the input data and sends the data as an output to the relay which is connected with the load. The relay will operate according to the sensor values and will be displayed in the LCD display. The presence of occupant will turn on the load depending on the lux value and will turn off if the occupant leaves.